The Comparison of the Conjunctions Used in Abstracts of English and Mathematics Students of Universitas Qomaruddin - Syafitri, Putri Nova; Mazidah, Eva Nur (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Kadiri, 2024)
The goal of this study was to identify the types of conjunctions in abstracts of English and mathematics thesis written by undergraduate students at Universitas Qomaruddin's English and mathematics departments. It demonstrates the similarity of conjunction usage in abstracts. This study uses a descriptive qualitative research design to look at 50 abstracts drawn from 25 English thesis abstracts and 25 mathematics thesis abstracts. By using the conjunction taxonomy developed by Halliday and Matthiessen (2014), the conjunctions in the abstract are categorized and then analyzed. The analysis's findings displayed that all abstracts use the three types of conjunctions—elaboration, extension, and enhancement. In the English department, in elaboration type found 8-word items with 5 variants. Extension type found 214-word items with 7 variants. Enhancement type found 87 words with 14 variants. However, the elaboration type found 12-word items with 2 variants in the mathematics department and extension type 244-word items with 5 variants. Enhancement type found 69-word items with 14 variants. The use of conjunctions in abstract of English and mathematics thesis shows many similarities to the selection and the amount of its use. These abstracts contain a few specific conjunctions but none of the others. Extension conjunctions—particularly those that are positive additives and use the word item